Peran Regulasi, Kinerja Keuangan, dan Inovasi Digital dalam Memperkuat Perbankan Syariah di Aceh - Aqlima Geubrina; Teuku Zulkarnain; Mariana Mariana (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
This study aims to analyze the role of regulation, financial performance, and digital innovation in strengthening the position of Bank Syariah Indonesia (BSI) in Aceh after the merger. The focus of this research includes evaluating the regulations governing BSI's operations, particularly the Aceh Qanun on Sharia Financial Institutions (LKS), which mandates financial institutions to operate according to Sharia principles. The study also assesses BSI's financial performance post-merger, focusing on asset growth, microfinance for SMEs, as well as the efficiency in managing financing and assets reflected in the decrease of Non-Performing Financing (NPF) and the increase in Return on Assets (ROA). Additionally, BSI’s digital innovations, such as e-banking services and the BYOND by BSI app, have improved accessibility and convenience for customers, particularly the younger generation. The study also identifies the challenges and prospects for BSI in maintaining public trust and expanding services in an increasingly competitive market. The findings indicate that regulation, solid financial performance, and technological innovation play a crucial role in strengthening BSI’s presence and supporting local economic growth in Aceh.